Predictive HR analytics mastering the HR metric - Edwards, Martin R.; Jang, Daisung; Edwards, Kirsten (London, United Kingdom New York, NY, USA Kogan Page, 2024)
This is the essential guide for HR practitioners who want to gain the statistical and analytical knowledge to fully harness the potential of HR metrics and organizational people-related data. The ability to use and analyse data has become an invaluable skill for HR professionals to not only identify trends and patterns, but also make well-informed business decisions. The third edition ofPredictive HR Analytics provides a clear, accessible framework for understanding people data, working with people analytics and advanced statistical techniques. Readers will be taken step-by-step through worked examples, showing them how to carry out analyses and interpret HR data in areas such as employee engagement, performance and turnover. Learn how to make effective business decision with this updated edition that includes the latest materials on biased algorithms and data protection, supported by online resources consisting of R and Excel data sets.
Previous edition: 2019.
Includes bibliographical references and index.
Keywords: Personnel management -- Statistical methods; Personnel -- Direction